In vivo rectal wall measurements during HDR prostate brachytherapy with MOSkin dosimeters integrated on a trans-rectal US probe: Comparison with planned and reconstructed doses. Issue 1 (January 2016) - Carrara, Mauro; Tenconi, Chiara; Rossi, Giulio; Borroni, Marta; Cerrotta, Annamaria; Grisotto, Simone; Cusumano, Davide; Pappalardi, Brigida; Cutajar, Dean; Petasecca, Marco; Lerch, Michael; Gambarini, Grazia; et al.
Abstract: Background and purpose: To study if MO Skin detectors coupled to a trans-rectal ultrasound (TRUS) probe may be used for in vivo dosimetry on the rectal wall surface during US-based HDR prostate brachytherapy and to quantify possible discrepancies between planned and delivered doses. Materials and methods: MO Skins are a specific type of MOSFET dosimeter optimized to measure dose in steep dose gradients on interfaces. Two MO Skins were assembled on a TRUS probe used for on-line treatment planning. Measurements of the dose to the rectal wall were performed over 18 treatment sessions and compared to the doses calculated on the pre-treatment plan ( DPRE ) and reconstructed on post-treatment images ( DPOST ). Results: Averages of the absolute differences between MO Skin readings and DPRE, MO Skin readings and DPOST and DPRE and DPOST were 6.7 ± 5.1%, 3.6 ± 1.9% and 6.3 ± 4.7%, respectively. Agreement between measurements and DPOST was significantly better than between measurements and DPRE (p = 0.002) and DPRE and DPOST (p = 0.004). Discrepancy between DPOST and DPRE correlated with the time required for treatment planning. Conclusion: MO Skin dosimeters integrated to the TRUS probe proved to be an accurate instrument for measuring the dose delivered to the rectal wall in HDR prostate brachytherapy. The delivered doses may differ significantly from those calculated in the treatment plan.